The Ninth Grade Students' Perception in Learning English Vocabularies Through Watching "Coco" Movie with Subtitle - Widiawati, Febi; Devanti, Yeni Mardiyana; Oktarini, Widya (Pubmedia Jurnal Pendidikan Bahasa Inggris, 2024)
Vocabulary is one of the important component should be learn by people who learns English. Movie can be an entertaining media and source for students to improve their language skills because movies represent real-life language by native speakers. The use of English movies can be different for every learners grade. This research was aimed to finding “The Ninth Grade Students’ Perception In Learning English Vocabularies Through Watching Coco Movie With Subtitle. To collect the data, the researcher used instruments of questionnaire. The researcher useD Descriptive Qualitative Method with 29 respondents from Ninth grade students from SMPN 8 Jember. The data analyzed by using Prof. Dr. Sugiyono those are data reduction, data display and conclusion drawing. Based on the data those were 9 students had a positive answered. From 3 students got 100% positive answered, 3 student got 75%, 3 students got 88% positive answer. 20 students had negative perception. 16 students got 50%, 4 students got 63% for negative perception. It showed that the total percentage of negative perception level is more higher than the positive percetions. Based on the data analyze it could be concluded that the use of COCO movie with subtitle can be used for learning activity but not for the first choice. Most of the students find difficulty when watching the movie because of the English Subtitle.